Association between alcohol consumption and incidence of type 2 diabetes mellitus in Japanese men: a secondary analysis of a Retrospective Cohort Study - Jing Song; Wei-Qian Lin (BMC Endocrine Disorders, 2023)
Abstract Background Alcohol consumption is known to be associated with an increased risk of type 2 diabetes (T2DM). However, the effect of alcohol intake on the incidence of T2DM remains controversial due to inconsistent results across studies. This study aimed to bridge the gap among available literature in order to better define the association between alcohol consumption and incidence of T2DM. Methods We performed a secondary analysis using open-access data from a retrospective Japanese cohort of 15,464 participants who underwent regular medical examinations at Murakami Memorial Hospital. All participants underwent an initial exam including a questionnaire survey, physical examination, and blood biochemical testing to establish a at baseline. The primary outcome was new-onset T2DM during the follow-up exam. Statistical analysis was conducted using Cox regression and Kaplan–Meier methods to assess the risk of alcohol consumption on T2DM. Results During a median follow-up time of 5.39 years, 373 new-onset T2DM events were observed. The cumulative risk of T2DM incidence was higher in the heavy alcohol consumption group vs. the other three groups: none/minimal, light, and moderate consumption (log-rank test, P = 0.0002). Multivariate Cox regression analysis indicated incidental T2DM was independently associated with alcohol consumption. The adjusted hazard ratio relative to the none/minimal consumption group was as follows: 1.02 (95% confidence interval: 0.71, 1.48) for light consumption, 1.06 (0.71, 1.57) for moderate consumption, and 2.06 (1.30, 3.24) for heavy consumption (P value = 0.024). Subsequent subgroup analysis confirmed the association between alcohol consumption and T2DM incidence in men, but not in women. Conclusion Heavy alcohol consumption was independently associated with an increased risk of new-onset T2DM in Japanese men.